MOTIVATION AND MATHEMATICS ACHIEVEMENT: A VIETNAMESE CASE STUDY - Lap Thi Tran; Tuan Son Nguyen (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2021)
Motivation is key to engaging students in studying mathematics and in improving their mathematics achievement. Although the related literature has explored the correlation between motivation and mathematics achievement, a research gap remains in terms of the empirical testing of these variables in the context of mathematics education in Vietnam. Thus, the current study aims to fill this gap by empirically testing the correlation between mathematics motivation and mathematics achievement among high school graduate students in Vietnam, using a quantitative approach to test hypotheses. The study adopted the Academic Motivation Toward Mathematics Scale for collecting data from students and received 680 responses. The main study findings are that amotivation negatively correlates with mathematics achievement, whereas introjected regulation, identified regulation and intrinsic motivation positively correlate with mathematics achievement. These findings provide a strong theoretical foundation for improving mathematics achievement by encouraging teachers to improve motivational conditions in mathematics classes in Vietnam.